Measurement of vapor-liquid equilibria for the binary systems of propane+1,1,1,2-tetrafluoroethane and 1,1,1-trifluoroethane plus propane at various temperatures - Lim, JS; Park, JY; Kang, JW; Lee, BG (ELSEVIER SCIENCE BV, 2006)
Isothermal vapor-liquid equilibrium data for the binary systems of propane + 1, 1, 1,2-tetrafluoroethane (HFC-134a) and 1,1,1-trifluoroethane (HFC-143a) + propane (HC-290) were measured at 273.15, 283.15, 293.15 303.15, 313.15 and 323.15 K, and 268.15, 278.15, 298.15, 308.15, and 318.15 K, respectively. The experiments were carried out using a circulation-type equilibrium apparatus with the measurement of temperature, pressure, and the compositions of the liquid and vapor phases. The experimental data were correlated with the Camahan-Starling-De Santis (CSD) equation of state. Calculated results showed good agreement with experimental data for both binary systems. It was found that these two systems have very strong positive azeotrope for all the temperature ranges studied here. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: MIXTURES; HFC-134A; PROPYLENE; HFC-152A